Digital promotion strategy for traditional cuisine: designing Maksuba cake videos as a culinary souvenir of Palembang city - Nanda Natasya; Rini Rini; Ummasyroh Ummasyroh (Jurnal Pariwisata Tourista, 2025)
Maksuba Cake is a traditional culinary product from Palembang with strong potential as a culinary souvenir. However, limited digital visual promotion hinders its sales growth. This study aims to design a promotional video that highlights the cultural value and visual appeal of Maksuba Cake. The research employed the ADDIE development model: Analysis, Design, Development, Implementation, and Evaluation. A 1-minute-17-second video was produced and published on Palembang Harum’s Instagram. The evaluation by business owners and media experts showed the video was informative, aesthetically appealing, and effective as a digital promotional tool. This strategy is expected to broaden market reach, strengthen product identity, and serve as a reference for promoting local culinary heritage through social media.